2018
DOI: 10.1038/s41467-018-06632-0
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of EGFR’s basal complexes reveals autoinhibition mechanisms in dimers and oligomers

Abstract: Our current understanding of epidermal growth factor receptor (EGFR) autoinhibition is based on X-ray structural data of monomer and dimer receptor fragments and does not explain how mutations achieve ligand-independent phosphorylation. Using a repertoire of imaging technologies and simulations we reveal an extracellular head-to-head interaction through which ligand-free receptor polymer chains of various lengths assemble. The architecture of the head-to-head interaction prevents kinase-mediated dimerisation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
147
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(172 citation statements)
references
References 79 publications
(165 reference statements)
24
147
1
Order By: Relevance
“…Such model assumes that activation happens in preformed dimers (39) (here detected for all ECD variants; SI Appendix, Fig. S5E) can explain mutants' dimerization-independent activity (15) and is supported by recent FRET data (40). Specifically, our data highlight N-TR1 flexibility and orientation as essential pieces to orchestrate ECD-KD coupling.…”
Section: Discussionsupporting
confidence: 78%
“…Such model assumes that activation happens in preformed dimers (39) (here detected for all ECD variants; SI Appendix, Fig. S5E) can explain mutants' dimerization-independent activity (15) and is supported by recent FRET data (40). Specifically, our data highlight N-TR1 flexibility and orientation as essential pieces to orchestrate ECD-KD coupling.…”
Section: Discussionsupporting
confidence: 78%
“…30 However, recent STORM imaging has revealed that even in the absence of EGF, the EGF receptors form complex oligomers on the plasma membrane, but the EGF binding induced a local geometric rearrangement of these receptors such that the intracellular tyrosine kinase domains could more readily cross-phosphorylate each other. 37 Hence, the enhanced PLA signal following EGF binding most likely reflects this local rearrangement in the pre-existing EGF-receptor clusters, rather than ligand-induced receptor dimerization. It should therefore be emphasized that in studying membrane-bound protein assemblies, super-resolution imaging and PLA-type experiments potentially reflect differing aspects of these supramolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This has been interpreted to indicate that EGF promotes the dimerization of the EGF receptor . However, recent STORM imaging has revealed that even in the absence of EGF, the EGF receptors form complex oligomers on the plasma membrane, but the EGF binding induced a local geometric rearrangement of these receptors such that the intracellular tyrosine kinase domains could more readily cross‐phosphorylate each other . Hence, the enhanced PLA signal following EGF binding most likely reflects this local rearrangement in the pre‐existing EGF‐receptor clusters, rather than ligand‐induced receptor dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the atomistic detail of Syt1 interations with the SNARE-Cpx complex and lipid bilayers, we performed all-atom molecular dynamics (MD) simulations at a microsecond scale. We took advantage of unique capabilities of the specialized Anton supercomputer designed for MD simulations [43,44], which enabled a breakthrough in simulating the protein dynamics at a time scale of microseconds [45,46]. We have recently employed these computational tools to investigate the conformational dynamics of Syt1 in the solution [47,48].…”
Section: Introductionmentioning
confidence: 99%